Analisis Kinerja Distribusi Air Irigasi pada Temuku di Subak - I Wayan Tika; Mentari Kinasih; Ni Nyoman Sulastri; Sumiyati Sumiyati; Ida Ayu Gede Bintang Madrini (Jurnal BETA (Biosistem dan Teknik Pertanian), 2023)
Disturbances in water distribution are also sometimes caused by the presence of rubbish and biasing factors (decreased discharge) also ignoring the flow of numbak (straight flow) and ngerirun (curved flow). With this understanding, farmers (krama subak) whose land is located downstream tend to get less water quota than they should. This research aims to determine the performance of irrigation water distribution management according to RPM values and criteria in traditional subak and semi-technical Subak. This research uses a descriptive quantitative method that explains events based on the RPM values of 30 buildings for (temuku) in Subak in Gianyar Regency. The research results showed that 30% had very poor irrigation water distribution performance, 30% had poor performance criteria, 13% had sufficient performance criteria, and 27% had good performance criteria. From these results, it is also possible to obtain a new dimension of the subak building using a proportional formula approach involving variables of the area of the subak provided with irrigation water, the area of the subak downstream, as well as a water flow disturbance coefficient of around 1.05 to 1.1.